Asymptomatic Significant Bacteriuria in the Non-pregnant Woman: II. Response to Treatment and Follow-up. Issue 5647 (29th March 1969) - Asscher, A. W.; Sussman, M.; Waters, W. E.; Evans, Joy A. S.; Campbell, H.; Evans, K. T.; Williams, J. Edmund
Abstract : Short courses of nitrofurantoin and ampicillin produced an immediate cure in 80% of adult non-pregnant bacteriuric women. Of the subjects so treated, 55% remained cured at the end of one year. Over the same follow-up period 36% of untreated bacteriuric women developed a spontaneous remission of bacteriuria. Treatment failed to prevent the development of symptomatic infection, and the reinfections which followed successful treatment were more commonly associated with the development of symptoms than the persistent or relapsing infections in untreated or unsuccessfully treated subjects. It is concluded that a search for bacteriuria in non-pregnant women is unlikely to be of value as a preventive measure, since in many instances it fails to detect urinary tract infection at an early stage and since treatment by methods suitable for large-scale use is ineffective.